Legitimising student activism in times of crisis: A discursive analysis of two Romanian youth organisations on Facebook (Revista Română de Jurnalism și Comunicare, 2025)
This paper explores how two major Romanian national student organisations (the National Council of Students – CNE, representing high school students, and the National Alliance of Student Organisations in Romania – ANOSR, representing university students) construct legitimacy as civic actors through Facebook activism during times of crisis. Focusing on the period 2019–2022, the study examines how these organisations navigated moments of political and social disruption, including the COVID–19 pandemic, the war in Ukraine, and national education reforms.Using the legitimation framework proposed by Van Leeuwen and Wodak (1999) and Vaara et al. (2006), along with the concept of destructive legitimation (Vestergaard & Uldam, 2022), the paper analyses Facebook posts through discourse analysis. Results indicate that both organisations employ strategies such as normalisation, authorisation, rationalisation, moral evaluation, and narrativisation to justify their activism, while also engaging in delegitimation of political opponents.The study contributes to understanding how student movements in post-socialist democracies use digital discourse to assert credibility and mobilise support.